Analisis Pengaturan Putaran Motor Satu Fasa Dengan Parameter Frekuensi Menggunakan Power Simulator (PSIM) - Dwi Hadidjaja Rasjid (Jurnal EECCIS, 2015)
Abstract-The Setting of a single-phase motor rotation can be performed in various ways, such as by adjusting the frequency of the motor, the voltage, motor resistor or increasing the number of motor poles.By using astable oscillator circuit, setting a single-phase motor rotation frequency parameters can be done by setting the value variabel resistor. Thyristor trigger circuit can be used to control a single-phase motor rotation. Thyristor trigger phase angle changes, caused changes in the frequency, followed by the change of motor rotation. Changes in the value of the variable resistor in PSIM simulation produced the single-phase motor rotation frequency changes. PSIM simulation is used to analyze single-phase motor rotation of the model simulation results of the transformer output voltage.PSIM simulation can visualize electronic basic circuit and minimize the failure of real circuit. Index Terms—Frequency, PSIM simulation, Single-Phase Motor, Thyristor